Shaking table tests and fragility analysis of an ancient timber structure subjected to mainshock-aftershock sequences - Chongyang Ye; Jianyang Xue; Rui Zhou; Huaiquan Ling; Dejun Song; Zhen He (Soil Dynamics and Earthquake Engineering, 2026)

SIRT7-mediated H3K79 desuccinylation modulates functional activities of goat ovarian granulosa cells - Yawen Li; Lei Wang; Shuaifei Song; Qiuyan Li; Ying Gong; Zihan Wang; Shiyi Yao; Zihan Ma; Yingping Xia; Cong Zhou; Xinyang Yao; Jia Luo; et al. (Theriogenology, 2026)

Rapid retreat of the East Asian summer monsoon at the end of the Holocene humid period accelerated the transition from broadleaf to pine forest landscapes in northern China - Linjing Liu; Xin Mao; Lei Song; Xingqi Liu; Dejun Wan; Gaolei Jiang; Jingsong Yang; Hongmei Zhao; Chengmin Wang; Hua Zhao; Rong Ma (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Supercritical CO2-assisted pressure homogenization for exfoliating natural graphite toward high-performance graphene cathodes in aluminum-ion batteries - Yue Wu; Jianmin Feng; Li Wang; Jiacheng Qiu; Xuan Song; Xuwang Fu; Ziqi Luo; Jiahan Ma; Xiaoyu Yu; Lei Dong; Yan Han; Conglai Long; et al. (Chemical Engineering Journal, 2025)

Characterization of Metal Contamination in a Lake of Southeast Hubei: Insights Into Dissolved and Particulate Fractions and Associated Health Risks - Zhiqi Song; Zipeng Zeng; Changlin Zhan; Shan Liu; Min Guo; Ziguo Liu; Fei Zhang; Dejun Wan (Water, Air, & Soil Pollution, 2025)

Transcriptome analysis reveals differences in postharvest fruit firmness changes between two Kiwiberry varieties - Zhao Liu; Jianyu Song; Yuying Li; Yanhong Cui; Zeyang Zheng; Kexin Zhu; Taiming Liang; Zhenpan Liu; Yang Sun; Dejun Liang (Horticulture, Environment, and Biotechnology, 2025)

New perspectives on water chemistry classification of travertine/tufa - Qunwei Dai; Ting Zhang; Dejun An; Jingwen He; Jie Cui; Qiongfang Li; Ronglin Xu; Faqin Dong; Zheng Dang; Qianxi Song (Applied Geochemistry, 2025)

Reliability assessment of using different heavy metals in remote sedimentary records to reconstruct historical pollution - Jiapeng Gao; Ruiting Song; Xinrui Wang; Kexin Wan; Jianle Zhang; Guanqi Shan; Dejun Wan; Shaogang Wang (Environmental Pollution, 2025)

Experimental and numerical analysis on seismic behavior of corner Dou-Gong bracket in ancient timber buildings - Dejun Song; Jianyang Xue; Chenwei Wu (Soil Dynamics and Earthquake Engineering, 2024)

Genome-wide association study revealed the reason for the decrease in grain iron concentration during wheat breeding process in China - Jianhui Ma; Yize Wang; Shuya Li; Qianqian Liu; Meng Yuan; Chunci Li; Daijing Zhang; Qingdong Zeng; Jianhui Wu; Chengxiang Song; Wei Li; Dejun Han; et al. (Field Crops Research, 2024)

Experimental and theoretical study on seismic behavior of Dou-Gong brackets on column under the load in overhanging and width directions - Dejun Song; Jianyang Xue; Chenwei Wu (Engineering Structures, 2024)

Sediment records of black carbon variations over the last two centuries in North China - Dejun Wan; Yongming Han; Lei Song; Dongliang Ning; Qingfeng Jiang (Science of The Total Environment, 2023)

Two-century sediment records of atmospheric mercury variations in North China and their relations with regional and global emissions - Dejun Wan; Handong Yang; Zhangdong Jin; Lei Song; Dongliang Ning; Longjuan Cheng; Qingfeng Jiang (Environmental Science and Pollution Research, 2023)

BMP6 regulates AMH expression via SMAD1/5/8 in goat ovarian granulosa cells - Lei Wang; Yukun Wang; Bijun Li; Yiyu Zhang; Shuaifei Song; Wenfei Ding; Dejun Xu; Zhongquan Zhao (Theriogenology, 2023)

A multi-proxy record of climate variations over the last millennium from Kulun-nuur Lake sediments, Inner Mongolia, north-central China - Xin Mao; Dejun Wan; Lei Song; Jingsong Yang; Linjing Liu; Gaolei Jiang; Junfeng Li; Xingqi Liu (Journal of Paleolimnology, 2021)

Record-breaking heat wave in southern China and delayed onset of South China Sea summer monsoon driven by the Pacific subtropical high - Kaiqiang Deng; Song Yang; Dejun Gu; Ailan Lin; Chunhui Li (Climate Dynamics, 2020)
We investigate a record-breaking heat wave in southern China (SC) and explore its association with the South China Sea (SCS) summer monsoon (SCSSM), using station observations and various reanalysis products. This heat wave event started in mid-May 2018 and persisted more than 15 days, when the maximum air temperature anomaly exceeded 6 °C. Meanwhile, the onset of the SCSSM was extremely late in 2018, primarily due to the intrusion of easterly winds over the SCS. We show that the anomalous easterlies over the SCS associated with the delayed SCSSM could block the moisture transport from the tropical oceans to SC, which led to decreased rainfall, increased surface radiation, and elevated probability of heat wave in SC during May 2018. Further analysis reveals that both SC heat waves and SCSSM were significantly affected by the Pacific subtropical high (PSH). The westward extension of the PSH can hinder the establishment of SCSSM via inducing easterly anomalies over the SCS, which reduces SC rainfall and results in a drier surface condition. Moreover, the westward displacement of the PSH may cause anomalously high pressures, descending air motions, and divergent winds over SC, which triggers above-normal air temperatures that are conducive to the occurrences of SC heat waves. This study also underlines the importance of Eurasian planetary wave trains in bridging the upstream climate variability and the changes in PSH during boreal spring, which could be used to improve the intra-seasonal predictions of SC heat wave and SCSSM onset.

Phosphorus adsorption and desorption characteristics of different textural fluvo-aquic soils under long-term fertilization - Yunhong Zhang; Shaomin Huang; Doudou Guo; Shuiqing Zhang; Xiao Song; Ke Yue; Keke Zhang; Dejun Bao (Journal of Soils and Sediments, 2019)

Further quantifying the fluxes and contributions of sources to modern sediment in Lake Qinghai, NE Tibetan Plateau - Dejun Wan; Zhangdong Jin; Fei Zhang; Hongyun Chen; Liumei Chen; Lei Song; Chao Song (Limnology, 2015)

Characteristics of the precipitation over the eastern edge of the Tibetan Plateau - Yueqing Li; Dejun Li; Song Yang; Cao Liu; Aihua Zhong; Ying Li (Meteorology and Atmospheric Physics, 2010)

Long-Term Toxicity Effects of Cadmium and Lead on Bufo raddei Tadpoles - Yingmei Zhang; Dejun Huang; Dongqin Zhao; Jing Long; Gang Song; An’na Li (Bulletin of Environmental Contamination and Toxicology, 2007)

Biosynthesis and bioactivity of trichosanthin in cultured crown gall tissues of Trichosanthes kirilowii Maximowicz - Hetian Lei; Jianjun Qi; Jingyuan Song; Dejun Yang; Yanzhi Wang; Yinling Zhang; Junshan Yang (Plant Cell Reports, 2006)

Cadmium induced MTs synthesis via oxidative stress in yeast Saccharomyces cerevisiae - Jianghai Liu; Yingmei Zhang; Dejun Huang; Gang Song (Molecular and Cellular Biochemistry, 2005)